Methodological basis of using triangulation in sociological research - Kuchko, Elena E. (Journal of the Belarusian State University. Sociology, 2023)
The article examines the specifics of qualitative and quantitative methodological approaches in sociology. The historical reconstruction of the dynamics of the development of these directions makes it possible to better understand their relationship, to determine the possibilities of their interaction in the study of social reality. In connection with this, the article presents the features of qualitative and quantitative methodological strategies of sociological research, their differences are justified. Positions regarding qualitative and quantitative strategies in Western and domestic sociology were considered. The importance of integrating methods, methodological strategies, theoretical paradigms in the research process is shown. Classical phase and priority-sequential models of methodological integration are considered. Various methods and methodological strategies have both advantages and disadvantages. Currently, the view on qualitative and quantitative methods has changed: they are considered as interacting, complementary. Triangulation as a strategy for the interaction of qualitative and quantitative approaches in the study of social problems using qualitative and quantitative methods of collecting and analysing sociological information increases the completeness and reliability of the information received expands research capabilities.